Soil N 2 O emissions during dry fallow periods - Rémi Cardinael; Louise Barton; Marc Corbeels; Johan Six; David Rowlings; Armwell Shumba; Regis Chikowo; Mark Farrell (Global Change Biology, 2024)
Shang et al. (2024) recently suggested to include nitrous oxide (N 2 O) emissions during the fallow period to better estimate N 2 O emission factors (EFs). We however highlighted several pitfalls of the proposed adjusted EFs for croplands in the specific case of dry subhumid, semiarid, and arid regions with dry fallow periods, these regions covering about 47% of the Earth's terrestrial area.